The impact of the master's program on the graduates / Farah Izzah Abdul Jalil - Abdul Jalil, Farah Izzah (2015)
Pharmacy Practice and Clinical Pharmacy (by coursework) are new programs in UiTM. These two programs were introduced in 2009 and were offered for pharmacists. Being new, the programs were never reviewed and evaluated for improvement. Objective: This study aimed to identify the graduates' perception on the masters programs that they have graduated from. Method: This was a quantitative survey study involving 70 postgraduate students who have graduated from both programs. The questionnaire was distributed using Google form. The data was analysed by using SPSS version 22. Result: 70 completed questionnaires were received. Majority of the graduates (n= 34, 49%) were within the age range of 31-35 years. 79% of the respondents (n=55) were graduates of pharmacy practice program. The main reason for taking up a master's degree program was for personal development (n=62) and the reasons for choosing UiTM was because of the location (57%) and reasonable and affordable fees ( 43%). The respondents agreed that the program had increased their confidence level (n=70, l 00% ), had great impact on their personal development (n=69, 99%) and improved their skills (n=67, 96%). Respondents also agreed that the program helped to prepare them to further their studies (n=63, 93%) in which 74% (n=52) ofrespondents reported planning to further studies to PhD. Many agreed that the duration of the program (3 semester) was appropriate (n=67, 96%) however a small number claimed that the sequencing of the courses in the program was inappropriate (n=8, 11 % ) and the classroom facilities were inadequate (n=3, 4%). In addition, 63% of the respondents (n=44) claimed that they will definitely recommend these programs to others. Conclusion: The graduates from both programs have good perception on these programs however some improvisations are still needed. Nevertheless, these programs are achieving their main goal that is to produce graduates with improved self-skills.